Association of the Emergence of Acyclovir-Resistant Herpes Simplex Virus Type 1 With Prognosis in Hematopoietic Stem Cell Transplantation Patients. (7th February 2017) - Kakiuchi, Satsuki; Tsuji, Masanori; Nishimura, Hidekazu; Yoshikawa, Tomoki; Wang, Lixin; Takayama-Ito, Mutsuyo; Kinoshita, Hitomi; Lim, Chang-Kweng; Fujii, Hikaru; Yamada, Souichi; Harada, Shizuko; Oka, Akira; et al.
Abstract: Background: Antiviral-resistant herpes simplex virus type 1 (HSV-1) has been recognized as an emerging clinical problem among patients undergoing hematopoietic stem cell transplantation (HSCT). Methods: A prospective observational study was conducted at a hematological center over a 2-year period. Oropharyngeal swab samples were serially collected each week from 1 week before and up to 100 days after HSCT and were tested for virus isolation. The HSV-1 isolates were tested for sensitivity to acyclovir (ACV). The prognosis of patients with ACV-resistant (ACVr) HSV-1 and the genetic background of the ACVr HSV-1 isolates were assessed. Results: Herpes simplex virus type 1 was isolated in 39 of 268 (15%) HSCT patients within 100 days after transplantation. Acyclovir-resistant HSV-1 emerged in 11 of these 39 patients (28%). The 100-day death rates of HSCT patients without HSV-1 shedding, those with only ACV-sensitive HSV-1 shedding, and those with ACVr HSV-1 shedding were 31%, 39%, and 64%, respectively. Patients with HSV-1, including ACVr HSV-1, shedding showed a significantly higher mortality rate. Relapsed malignancies were a significant risk factor for the emergence of ACVr HSV-1. Acyclovir resistance was attributable to viral thymidine kinase and DNA polymerase mutations in 6 and 5 patients, respectively. Conclusions: Herpes simplex virus type 1, including ACVr HSV-1, shedding was associated with poorer outcome in HSCT patients, even if HSV disease did not always occur. Patients with relapsed malignancies were at especially high risk for the emergence of ACVr HSV-1.